On the theoretical efficacy of quantitative easing at the zero lower bound - Paola Boel; Christopher J. Waller (Sveriges Riksbank, 2015)
We construct a monetary economy in which agents face aggregate demand shocks and heterogeneous idiosyncratic preference shocks. We show that, even when the Friedman rule is the best interest rate policy the central bank can implement, not all agents are satiated at the zero lower bound and therefore there is scope for central bank policies of liquidity provision. Indeed, we find that quantitative easing can be welfare improving even at the zero lower bound. This is because such policy temporarily relaxes the liquidity constraint of impatient agents, without harming the patient ones. Moreover, due to a pricing externality, quantitative easing may also have benficial general equilibrium effects for the patient agents even if they are unconstrained in their holdings of real balances. Last, our model suggests that it can be optimal for the central bank to buy private debt claims instead of government debt.
Keywords: E40; E50; 330; Money; Heterogeneity; Stabilization Policy; Zero Lower Bound; Quantitative Easing